Mediação Intercultural: formação, ação e reflexão - Silva, Ana Maria Costa e; Costa, Maria Elisabete Guedes Pinto da (2022)
Mediação Intercultural: Formação, Ação e Reflexão (Intercultural Mediation: Training, Action and Reflection) is the title of this book, which assumes a fundamentally pedagogical approach. It aims to provide a pedagogical support manual for intercultural mediators' initial and continuous training. For this purpose, it addresses the theoretical, ethical, methodological and praxeological foundations of intercultural mediation through several experts and professionals' contributions. The first part provides the background and basis for intercultural mediation through its scientific, social and political framework, allowing for understanding and configuring it in complex, multicultural, multi-ethnic and multi-religious societies. The second part focuses on the training and practice of intercultural mediation. According to the editors, this work contributes to the enhancement and dissemination of intercultural mediation through conceptual, methodological, training, action and (self)supervision proposals stemming from collaborative training, action and research processes.